FORMATION OF AN EFFICIENT SYARIAH STOCK PORTFOLIO USING THE MARKOWITZ MODEL ON THE JAKARTA ISLAMIC INDEX - Nadia Magvira; Khusnul Khatimah; Nursan Haryanto; Sarasrina; Nur Sipa; Serli Alifia; Suriani M (Journal Informatic, Education and Management (JIEM), 2026)
This study analyses the formation of an efficient sharia stock portfolio using the Markowitz Model on banking stocks in the Jakarta Islamic Index (JII) in 2025, namely BRIS (Bank Syariah Indonesia Tbk), BTPS (Bank BTPN Syariah Tbk), and BANK (Bank Aladin Syariah Tbk), with daily closing stock price data from the IDX and Yahoo Finance processed using R Studio to calculate historical returns, expected returns, risk (standard deviation ) , covariance, and correlation; The results show that BTPS has the highest expected return (0.10795%) but the highest risk (0.0283), while BANK is the most stable (risk 0.0183%), with moderate correlation between stocks (0.09-0.46), resulting in an optimal portfolio in the form of the highest risk portfolio (100% BTPS, return 0.03%, risk 2.87%) and the lowest risk (22% BRIS, 16% BTPS, 62% BANK, return 0.04%, risk 1.51%), so that the Markowitz Model is proven to be effective in balancing risk-return through diversification for sharia investors.